Will Digital Technologies Transform Agriculture in Developing Countries? - Deichmann, Uwe; Goyal, Aparajita; Mishra, Deepak (World Bank, Washington, DC, 2016)
Mobile phones and the internet have significantly affected practically all sectors of the economy, and agriculture is no exception. Building on a recent World Bank flagship report, this paper introduces a concise framework for describing the main benefits from new information and communications technologies. They promote greater inclusion in the broader economy, raise efficiency by complementing other production factors, and foster innovation by dramatically reducing transaction costs. The paper reviews the recent literature on corresponding technology impacts in the rural sector in developing countries. Digital technologies overcome information problems that hinder market access for many small-scale farmers, increase knowledge through new ways of providing extension services, and they provide novel ways for improving agricultural supply chain management. Although there are many promising examples of positive impacts on rural livelihoods--or "digital dividends"--often these have not scaled up to the extent expected. The main reason is that technology can only address some, but not all, of the barriers faced by farmers in the poorer countries.